2019
DOI: 10.3390/ijms20061328
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin Reduces Myofibroblast Activities in Oral Submucous Fibrosis by LINC00974 Inhibition

Abstract: Oral submucous fibrosis (OSF) is an oral precancerous condition associated with the habit of areca nut chewing and the TGF-β pathway. Currently, there is no curative treatment to completely heal OSF, and it is imperative to alleviate patients’ symptoms and prevent it from undergoing malignant transformation. Arctigenin, a lignan extracted from Arctium lappa, has been reported to have a variety of pharmacological activities, including anti-fibrosis. In the present study, we examined the effect of arctigenin on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Rheumatoid arthritis (RA) is characterized by TNF‐α and IL‐1β‐driven synovial inflammation that results in the bone and cartilage destruction . Despite the fact that TNF‐α is a pivotal inflammatory cytokine in acute joint swelling, IL‐1β is considered as the dominant cartilage destructive cytokine and its production may occur in TNF‐α‐independent manner .…”
Section: Therapeutic Potential Of Il‐1ra Producing Mscs In the Treatmmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatoid arthritis (RA) is characterized by TNF‐α and IL‐1β‐driven synovial inflammation that results in the bone and cartilage destruction . Despite the fact that TNF‐α is a pivotal inflammatory cytokine in acute joint swelling, IL‐1β is considered as the dominant cartilage destructive cytokine and its production may occur in TNF‐α‐independent manner .…”
Section: Therapeutic Potential Of Il‐1ra Producing Mscs In the Treatmmentioning
confidence: 99%
“…IL, interleukin; IL-1Ra, IL-1 receptor antagonist; MSC, mesenchymal stem cell; PGE2, prostaglandin E2; TNF-α, tumor necrosis factor alpha; TLR, toll-like receptor 6 | THERAPEUTIC POTENTIAL OF IL-1RA PRODUCING MSCS IN THE TREATMENT OF JOINT DISEASES Rheumatoid arthritis (RA) is characterized by TNF-α and IL-1β-driven synovial inflammation that results in the bone and cartilage destruction. 66,67 Despite the fact that TNF-α is a pivotal inflammatory cytokine in acute joint swelling, IL-1β is considered as the dominant cartilage destructive cytokine and its production may occur in TNF-α-independent manner. 66 Therefore, IL-1Ramediated inhibition of IL-1β-driven synovial inflammation has crucially important protective role in the pathogenesis of RA.…”
Section: Il-1ra-expressing Mscs As a New Therapeutic Agent In The Cmentioning
confidence: 99%
“…Due to their chemical structure, phytoestrogens can be classed as isoflavones and lignins. Arctigenin (Ar, Figure 1) is a lignin phytoestrogen extracted from Arctium lappa (Gao, Li, Zhang, & Zeng, 2008) that displays anti-inflammatory (Gao, Yang, & Zuo, 2018), antioxidant (Wu et al, 2014), antifibrosis (Lin et al, 2019), and antitumor effects (Maxwell, Chun, Lee, Kim, & Nam, 2017). In preliminary experiments, we found that arctigenin promotes the differentiation of bone marrow mesenchymal stem cells (BMSCs) of ovariectomized (OVX) rats into osteoblasts, leading to anti-osteoporosis effects.…”
Section: Introductionmentioning
confidence: 99%
“…Transforming growth factor-β (TGF-β) is a major cytokine involved in OSF progression. It regulates the expression of α-SMA and type 1 collagen in myofibroblasts [47][48][49]. Studies have shown arecoline induced connective tissue growth factor (CTGF) biosynthesis via reactive oxygen species (ROS) and the NF-κB, JNK, and p38 MAPK pathways in buccal mucosal fibroblasts [35,48].…”
Section: Inflammatory Cytokines and Growth Factorsmentioning
confidence: 99%